Fraksinasi dan Identifikasi SenyawaAntioksidan pada Eksb-ak Etanol buah Goji beny(Lycium barbarum linn.) secaraKromatografi Kolom - Albrian, Diga; Wijaya, Sumi; Setiawan, Henry Kurnia (Jurnal Farmasi Sains dan Terapan, 2013)
Goji berry fruit (Lycium barbarum), familia Solanac'eae, is a red berry fruit. The chemical compounds contained in this fruit are polysaccharides, zeaxanthin and beta-carotene. Activity of the chemical compounds is still considered as a family of antioxidant compounds, which are used as a medicine to cure the diseases caused by the presence of free radicals such a atherosclerosis, cancer, liver cirrhosis, hypertension and diabetes. The research will be carried on fractionation and identification of the ethanol extract of Goji berry fruit to obtain compounds that have antioxidant power using chromatographic column method and DPPH method. The isolated compounds will be identified using methods phytochemica/s screening, TLC, UV-Vis spectrophotometer and infrared spectrophotometer. The result showed that secondary metabolites of Goji berry fruit which are potential as antioxidant compound were flavonoid (flavono/s or flavones). The isolated compound had higher antioxidant activity compare to the ethanol extract of Goji berry fruit Flavonoids are the major compounds that have antioxidant capacity. Whereas, the ethanol fraction of Goji berry fruits has the best antioxidant activity than the ethanol extract Keywords: Antioxidant, Goji berry, DPPH and chromatographic column